B cell sub-types following acute malaria and associations with clinical immunity. (December 2016) - Sullivan, Richard; Ssewanyana, Isaac; Wamala, Samuel; Nankya, Felistas; Jagannathan, Prasanna; Tappero, Jordan; Mayanja-Kizza, Harriet; Muhindo, Mary; Arinaitwe, Emmanuel; Kamya, Moses; Dorsey, Grant; Feeney, Margaret; et al.
Abstract Background Repeated exposure toPlasmodium falciparum is associated with perturbations in B cell sub-set homeostasis, including expansion atypical memory B cells. However, B cell perturbations immediately following acute malaria infection have been poorly characterized, especially with regard to their relationship with immunity to malaria. Methods To better understand the kinetics of B cell sub-sets following malaria, the proportions of six B cell sub-sets were assessed at five time points following acute malaria in four to 5 years old children living in a high transmission region of Uganda. B cell sub-set kinetics were compared with measures of clinical immunity to malaria—lower parasite density at the time of malaria diagnosis and recent asymptomatic parasitaemia. Results Atypical memory B cell and transitional B cell proportions increased following malaria. In contrast, plasmablast proportions were highest at the time of malaria diagnosis and rapidly declined following treatment. Increased proportions of atypical memory B cells were associated with greater immunity to malaria, whereas increased proportions of transitional B cells were associated with evidence of less immunity to malaria. Conclusions These findings highlight the dynamic changes in multiple B cell sub-sets following acute, uncomplicated malaria, and how these sub-sets are associated with developing immunity to malaria.